2018
DOI: 10.1542/peds.2017-1026n
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Young Children From Tobacco Smoke Exposure: A Pilot Study of Project Zero Exposure

Abstract: A program based on motivational interviewing and demonstrating TSE and contamination to parents in a concrete and easily understandable way is a promising approach to protect children from TSE. Further research is needed to enhance current methods of measurement and assess promising interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A preliminary version of the questionnaire was piloted with 22 parents in smoking families who were participants in a pilot study of Project Zero Exposure [ 24 ]. This initial version contained 10 photos and 10 descriptions of people smoking around children, to be rated according to the level of perceived exposure on a scale of 1 to 3.…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary version of the questionnaire was piloted with 22 parents in smoking families who were participants in a pilot study of Project Zero Exposure [ 24 ]. This initial version contained 10 photos and 10 descriptions of people smoking around children, to be rated according to the level of perceived exposure on a scale of 1 to 3.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Yücel, Öcek, & Çiceklioğlu (2014), it was found that smoking at home causes an increase in the amount of cotinine in children's urine. In another study, it has been found that informing the measurement results of the cotinine levels in the hair of the children who are exposed to smoking and the number of nicotine and particles in the air was effective for parents to quit smoking (Rosen et al, 2018) Smoking in the house increases the risk of passive smoking. Especially children and pregnant women are at risk in this regard (Johansson et al, 2004.…”
Section: Discussionmentioning
confidence: 99%
“…An optimistic note, however, is sounded by the findings of Oates et al indicating that cessation of TSE will lead to a reversal of its adverse effects, with a decrease in pulmonary exacerbations and improvements in FEV1 and weight. Feasible programs that can be initiated in the setting of pediatric practices have been shown to reduce second-hand TSE [13] and pediatric practice-based programs to counsel parents on smoking cessation have some (if limited) proven effectiveness [14] . Active intervention for smoking parents has been endorsed by the American Academy of Pediatrics [15] ; surveys of parents show that advice on smoking cessation from their child's physician would be welcomed by most parents [16] .…”
mentioning
confidence: 99%